GE_GERICHTE P/10947/2023 vom 3. Februar 2025 - GE Cour de justice (2025)
CLASSEMENT DE LA PROCÉDURE;CONCUBINAGE;MÉNAGE COMMUN;PLAINTE PÉNALE;LÉSION CORPORELLE;VOIES DE FAIT;DÉLAI;RETARD;DROIT D'ÊTRE ENTENDU | CPP.319.al1.letd; CP.123.al6.ch2; CP.126.letc.ch2; CP.31; Cst.29.al2